ANALYSIS OF THE FACTORS THAT INFLUENCE COSTUMER SATISFACTION AT PT. BPRS GEBU PRIMA - Azizah, Noviwan; yati, Rahma (Universitas Muhammadiyah Sumatera Utara, 2023)
The purpose of this study was to determine the effect of sharia compliance and assurance on customer satisfaction at PT. BPRS Gebu Prima. The type of research in this thesis is quantitative research and the data used is in the form of primary data. Data collection techniques in this study used questionnaires and documentation with a population of all customers of PT. BPRS Gebu Prima and a sample of 78 people using the Slovin formula. Data analysis techniques with descriptive tests, validity and reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Processing of data using the SPSS program version 23.0. The results of this study are that the Sharia Compliance variable (X1) has an effect on customer satisfaction as can be seen from tcount ttable (3.779 1.992) and its significance level is less than 0.05 (0.000 0.05). The assurance variable (X2) has an effect on customer satisfaction as can be seen from tcount ttable (4.740 1.992) and its significance level is less than 0.05 (0.000 0.05). Simultaneously, sharia compliance and assurance have a significant and significant effect on customer satisfaction at PT. BPRS Gebu Prima, namely 0.511 or 51.1%.